FOREWORD FROM HANDLING EDITOR - 13TH EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2024)
We are delighted to present the 13th edition of JESSD, published in December 2024. We have selected ten of the best articles for this edition that related with topic of Environmental Science and Sustainable Development.